Effect of Sapindus rarak powder as feed additive on performance and lipid profile of broiler chicken infected by Eimeria tenella - Pasaribu, Tiurma; Wina, Elizabeth; ., Sumiati; Setiyono, A; Astuti, Dewi Apri (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Sapindus rarak fruits have bioactive compound named saponin which are potential to inhibit growth of protozoa and reduce cholesterol. This study was conducted to evaluate effect of lerak (Sapindus rarak) powder as microparticle on performance and lipid profile of chicken broiler that was infected by Eimeria tenella. A total of150headsof DOCwere assign to recive on of5 treatments: T1 (K+, TAk, TSRa, TIE), T2 (K-, TAk, TSRa, IE), T3 (Sal, IE), T4 (Sra 2,5, IE), and T5 (Sra 1,25, IE); each treatment consisted of 6replications with 5birds per replications in battery cage for 34 days. All chickens except those in control positive treatment (non-infected, non-medicated) were inoculated orally with 6000 oocysts E. tenella on the 14th day of age. Variables measured were body weight gain, carcass, OPG (oocysts pergram of faeces), lipid profile, and mortality. Treatment with S. rarak, dose of 1.25g/kg was not significantly different from the salinomycin treatment on BWG and feed conversion. Percentage of carcassand organs and blood cholesterol concentration were not significantly differentin all treatments, but blood triglyceride at S. rarak addition with doseof 2.5, 1.25g/kg and salinomycin addition with dose of 0.5g/kg, and negative control were lower than positive control. While number of OPG in faeces (days 14-34) showed that S. rarak powder with dose of 2.5 and 1.25g/kg suppressed the development of oocystsof E. tenella. In conclusion, S. rarak microparticle (75Âµm) can be used as feed additive to replace salinomycinas coccidiostat. Key Words: Sapindusrarak Powder, Chicken, Performance, Blood Lipid Profile, Eimeria tenella